Artificial Intelligence and (Im)partiality in Judicial Decisions - Melro, Ana (Law, State and Telecommunications Review, 2024)
[Purpose] The paper aims to understand the relationship between Artificial Intelligence, Law and Discourse (namely, the one used in judicial decisions). To then analyze how the interference of Artificial Intelligence in judicial decisions can guarantee impartiality and if that interference should be the intention. [Methodology/Approach/Design] For this purpose, a theoretical reflection was carried out around the central concepts: Law, judicial decisions, impartiality, and artificial intelligence. For this, bibliographical research was carried out. [Findings] Artificial Intelligence (AI) is a current reality. A tautology that has been repeated so that individuals do not forget the challenges they face as a result. Thus, the courts, the judicial professions, and the law, are being confronted with this “new” reality, whether in a challenge format or from the perspective of the facilities that AI brings coupled. It remains to be seen, then, what will be the principles of law. If AI will interfere in judicial decision-making (as has already been tested), what will become of the principle of impartiality? And is this a principle that is intended to be maintained or even currently exists? The article goes through all these corners: the intertwining between discourse, law and AI; impartiality and AI as a decision-maker.